Transformasi Digital dan Strategi Adaptasi UMKM dalam Menghadapi Era Ekonomi Digital di Indonesia - Fikri Alfahmi Siregar; Okta Viani Kristin; Nabila Boru Lubis; Azri Nuansa Indah; Olivia Sembiring; Lokot Muda Harahap (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid development of digital technology has significantly transformed economic activities, including the operations of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Digital transformation enables MSMEs to enhance operational efficiency, expand market reach, and improve competitiveness in an increasingly dynamic business environment. However, many MSMEs still face challenges such as limited digital literacy, inadequate resources, and lack of effective digital strategies. This study aims to analyze digital transformation and adaptation strategies of MSMEs in facing the digital economy era in Indonesia. The research employs a qualitative descriptive approach using a literature review method by analyzing various academic sources, including journals, books, and research reports related to MSME digitalization. The findings indicate that digital transformation plays a crucial role in improving MSME performance and competitiveness through the utilization of digital platforms such as social media, e-commerce, and digital payment systems. In addition, MSMEs adopt various adaptation strategies, including digital marketing, product innovation, and service quality improvement to respond to changing consumer behavior. Nevertheless, the implementation of digital transformation is still hindered by several factors, including low digital literacy, limited technological infrastructure, and insufficient support systems. Therefore, collaboration between government, educational institutions, and private sectors is essential to strengthen the digital ecosystem and support sustainable MSME development in the digital economy era.